PEMANFAATAN DIGITAL MARKETING BAGI PENGEMBANGAN USAHA MAKANAN DAN MINUMAN - Indriyani, Ratih; Kempa, Sesilya (Jurnal Kreativitas dan Inovasi (Jurnal Kreanova), 2022)
Micro, Small and Medium Enterprises have limitations in running their business in terms of awareness in the market, limited scope of sales area, and facing competition from local and other regions. This is a challenge for developing micro, small and medium scale enterprises. This community service activity is held on a service-learning basis in the form of business assistance in the food and beverage sector. The mentoring stage itself starts from the debriefing stage to monitoring. The purpose of this activity is to find out the obstacles and challenges faced by MSMEs and develop digital marketing that can support their business. Digital marketing is applied specifically in making social media suitable for MSMEs. Digital marketing is expected to expand market reach. The results of this activity show that the use of digital technology can change the way MSMEs connect with their consumers. he use of social media helps promote products to a wider audience, as well as helps wider product recognition. The characteristics and development needs of MSMEs also cause differences in the need to apply different digital marketing methods.